PENINGKATAN KEMAMPUAN BACA TULIS HURUF AL-QUR’AN MELALUI METODE TAMAM PADA MAHASISWA FAKULTAS SAINS DAN TEKNOLOGI UIN SUNAN GUNUNG DJATI BANDUNG - Gina Giftia AD (JURNAL ISTEK, 2014)
As a divine revelation, the Holy Quran essentially is the guidelines and instructions which guide human kind to achieve prosperity and happiness in the world and the Hereafter. However, in reality there are many Muslims who can not read the Holy Qur'an. Many factors are behind this; one of them is the use of method in teaching how to read and write Hijaiyah Letter (the Holy Quran.) This study aims to examine if there is any increase in ability to read and write Hijaiyah letters among students of Faculty of Science and Technology, UIN Sunan Gunung Djati, Bandung after using Tamam method. This research is using quasi-experimental one group pretest posttest method. This study concluded that Tamam method is very systematic and effective in teaching how to read and write Hijaiyah letter where it shows the successful in increasing the ability of reading and writing Hijaiyah letters among students.